Feasibility of utilizing ultra-low-dose contrast medium for pancreatic artery depiction using the combination of advanced virtual monoenergetic imaging and high-concentration contrast medium: an intra-patient study - Juan Li (SpringerOpen, 2021)
Abstract Objectives The least amount of contrast medium (CM) should be used under the premise of adequate diagnosis. The purpose of this study is to evaluate the feasibility of utilizing ultra-low-dose (224 mgI/kg) CM for pancreatic artery depiction using the combination of advanced virtual monoenergetic imaging (VMI+) and high-concentration (400 mgI/mL) CM. Materials and methods 41 patients who underwent both normal dose CM (ND-CM, 320 mgI/kg) and low dose CM (LD-CM, 224 mgI/kg) thoracoabdominal enhanced CT for tumor follow-up were prospectively included. The VMI+ at the energy level of 40-kev for LD-CM images was reconstructed. CT attenuation, signal-to-noise ratios (SNRs), and contrast-to-noise ratios (CNRs) of the abdominal artery, celiac artery, and superior mesenteric artery (SMA) and qualitative scores of pancreatic arteries depiction were recorded and compared among the three groups (ND-CM, LD-CM, and VMI+ LD-CM images). ANOVA and Friedman tests were used for statistical analysis. Results All quantitative and qualitative parameters on LD-CM images were lower than that on ND-CM images (all p < 0.01). There were no significant differences of all arteries’ qualitative scores between ND-CM and VMI+ LD-CM images (all p > 0.05). VMI+ LD-CM images had the highest mean CT and CNR values of all arteries (all p < 0.0001). The CM volume was 52.6 ± 9.4 mL for the ND-CM group and 37.0 ± 6.7 mL for the LD-CM group. Conclusion Ultra-low-dose CM (224 mgI/kg) was feasible for depicting pancreatic arteries. Inferior angiographic image quality could be successfully compensated by VMI+ and high-concentration CM.